Metode Parenting Anak Menurut Pemikiran Imam Al Ghazali - Annisaa Nur Faudillah; Masganti Sitorus; Nur Sa’adah; Alya Sabrina Ramadhani (Inovasi Pendidikan dan Anak Usia Dini, 2025)
Parenting plays a crucial role in shaping a child's personality and religious values ​​from an early age. This study aims to examine the concept of parenting from an Islamic perspective, particularly according to the views of Imam Al-Ghazali, a prominent Islamic scholar and thinker. The method used was a literature review with a descriptive analytical and historical approach. The results show that Islamic parenting, according to Al-Ghazali, is based on the principles of monotheism, faith, and noble morals derived from the Quran and Sunnah. Al-Ghazali viewed children as a trust from Allah, born in a state of fitrah (purity) and as potential beings who are the hope of the community. Educating children must be done from an early age because childhood is a golden period that is very decisive in character formation. The parenting methods recommended by Al-Ghazali include: (1) the habituation method to shape character through continuous practice; (2) the role model method, where parents serve as direct role models for children; (3) the storytelling method to instill moral values; (4) the advice method with a compassionate approach; and (5) reward and punishment methods applied wisely. Al Ghazali's parenting concept emphasizes the importance of parents' role in creating a conducive environment for children's spiritual, moral, and social development, which not only impacts worldly life but also the afterlife. This research contributes to the idea of ​​the urgency of implementing Islamic teachings in educating and raising children in the digital era, which is full of various challenges.